Designing a Virtual Environment to Develop the Female Students' Skills in Draping on the Mannequin - Dr. Salia Hassan Khafaji (Journal of Arts, Literature, Humanities and Social Sciences, 2022)
The virtual education forming a great importance in the economic and social development and that due to its importance to the individuals in particular and to society in general, It is a method of transmitting knowledge, communicating and obtaining information through a set of advanced educational tools that can present an added value on the education by the traditional methods. It is a widespread phenomenon and a means to transcend the geographical distances. The research aims to: 1- Designing a virtual environment to develop the female students’ skills in draping on the mannequin. 2- Measuring the effectiveness of the virtual environment by giving the female understudies with the information and skills for draping on the mannequin. 3- Studying the foundations of employing the interactive teaching methods to achieve the objectives of the virtual environment in developing knowledge and skills. 4- Determining the basic requirements for building the virtual learning environments in the educational institutions. The research reached to: 1- There are statistically significant differences between the mean scores of the female understudies within the virtual environment before and after the application in favor of the post application. 2- There are statistically significant differences among the mean scores of the female understudies within the acquired knowledge before and after the application in favor of the post test. 3- There are statistically significant differences among the mean scores of the female understudies within the acquired skills before and after the application in favor of the post test. The research recommended: Keeping pace with the global trends to take benefit from the modern information technologies in the processes of education. Designing virtual environments for other curricula in the field of clothing and textiles. 3- Take benefit from the regional and global experiences of the virtual learning environments in higher education institutions.